2022
DOI: 10.18863/pgy.931572
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19’un Öğrencilerin Stres, Anksiyete, Depresyon, Korku Düzeylerine Etkisi: Sistematik Derleme

Abstract: Bu araştırmada, Covid-19 pandemisi sürecinde öğrencilerin stres, anksiyete, depresyon, korku düzeyleri ve ilişkili faktörleri, literatür taraması yaparak incelenmesi amaçlanmıştır. Araştırmada, 27.12.2019-30.12.2020 tarihleri arasında elektronik veri tabanları "Covid-19, pandemi, ruh sağlığı, öğrenciler", "Covid-19, pandemic, mental health, students" anahtar sözcükleri kullanılarak taranmıştır. Tarama sonucunda 562 çalışmaya ulaşılmış olup 22 makale çalışmaya dahil edilmiştir. Yaş aralığı 14-33 arasında olan ö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 3 publications
0
4
0
4
Order By: Relevance
“…Upon the review of the mean pretest BAI scores of participants in experimental and control groups before the horticultural therapy, it can be said that participants in both study groups had moderate anxiety, and in terms of anxiety levels, the two study groups were homogeneous. In a systematic review performed by Didin et al to analyze young individuals' anxiety levels throughout the COVID-19 pandemic period and examine associated factors, it was identi ed that individuals had moderate anxiety [22]. In the study performed by Ergin et al with students of the faculty of medicine, it was found that students had medium levels of anxiety [23].…”
Section: Discussionmentioning
confidence: 99%
“…Upon the review of the mean pretest BAI scores of participants in experimental and control groups before the horticultural therapy, it can be said that participants in both study groups had moderate anxiety, and in terms of anxiety levels, the two study groups were homogeneous. In a systematic review performed by Didin et al to analyze young individuals' anxiety levels throughout the COVID-19 pandemic period and examine associated factors, it was identi ed that individuals had moderate anxiety [22]. In the study performed by Ergin et al with students of the faculty of medicine, it was found that students had medium levels of anxiety [23].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the distal context (exosystem), changes made in the exam systems by education administrators might affect students. In a study conducted in Turkey (İnkaya, 2019) a sudden change in the 2018 exam system caused more exam anxiety among students compared to the students who entered the same exam in the following years. Besides, personality characteristics, gender, and age at which the exam was taken also affect anxiety levels.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…From an ecological perspective, students’ personality characteristics such as perfectionism (Arana & Furlan, 2016), irrational beliefs (Rohsenow & Smith, 1982), and gender (Kumaran & Kadhiravan, 2015; Trifoni & Shahini, 2011) can be be associated with exam anxiety. In the distal context, changes made in the exam system by education administrators (see İnkaya, 2019) can also affect exam anxiety among students. In proximal contexts, on the other hand, some scholars (e.g.,: Peleg-Popko & Klingman, 2002; Zeidner & Mathews, 2005) highlighted parental and familial factors regarding their relation to student’s exam anxiety.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Çalışmada bu amaçla hazırlanan "Tiyatro ile COVID-19 hastalığından korunmayı öğreniyorum" eğitiminden sonra öğrencilerin hastalığa ilişkin tutum ve korku puanları tekrar değerlendirilmiş ve eğitim öncesine göre daha düşük düzeyde korkuya (16.76±6.81) ve daha yüksek düzeyde olumlu tutuma (85.80±32.65) sahip oldukları tespit edilmiştir (p<0.05). COVID-19'un öğrencilerin stres, anksiyete, depresyon ve korku düzeylerine etkisinin incelendiği bir sistematik derleme çalışmasında bireylerin COVID-19'a ilişkin bilgi düzeyi ve alınan önlemlerin yeterliliğine olan inançlarının kaygı ve korku düzeyini etkilediği bildirilmiştir (Didin, Yavuz, & Yazıcı, 2022).…”
Section: Discussionunclassified